ACTIVATING STUDENTS’ PARTICIPATION THROUGH COMMUNICATIVE STRATEGIES: GRAMMAR SUBJECT IN STKIP YAYASAN ABDI PENDIDIKAN PAYAKUMBUH - Fadila Taslim (Proceedings of ISELT FBS Universitas Negeri Padang, 2017)
This study was an action research aiming at revealing the students’ Participation in communcating ideas in Grammar course. Sometimes, Communicating idea become an uneasy work. The difficulties commonly found in relation to the lackness of vocabulary. Yet, the learners makes some efforts in overcoming their problem called communicative strategies. The Subject was 25 students of Grammar IV subject of English Study Program at STKIP Yayasan Abdi Pendidikan. The data were collected by using observation sheet, recording and lecturer’s journal. This study ran for two cycles. In the second cycle, it was shown that there was gradual improvement of the participation shown the increase of the students’ participation in communicating their ideas. It was significant because the aspects of the participation such as the students’ enthusiasm in finding the answer arose untill 76 % (very active); discussing actively was 56%(active), asking question was 60%(active), answering question was 52%(active) and noting down was 92%(very active). It means that the students enjoyed and were not reluctant  in transfering their ideas anymore. The most frequence strategies in communicating their ideas was fillers and literal translation respectively. So, these strategies was a motivation for them to communicate their thoughts eventhough they were up against some problems on vocabulary.